99m Tc glucarate as a potential radiopharmaceutical agent for assessment of tumor viability: From bench to the bed side - Partha Choudhury; E. Savio; K. Solanki; O. Alonso; A. Gupta; J. Gambini; Dinesh Doval; P. Sharma; M. Dondi (World Journal of Nuclear Medicine)
Several radiotracers have been used for assessing cell death, whether by necrosis or apoptosis. 99m Tc glucarate, which has initially been reported to be concentrating/accumulating in myocardial infarction or zones of cerebral injury, has also shown some tumor-seeking properties in a few preliminary studies. Under International Atomic Energy Agency (IAEA)′s coordinated research program, we report here the standardization, quality control, and clinical evaluation (detection, evaluation of response, and comparison with 18 F Fluorodeoxyglucose) of this tracer in well-characterized lung cancer and head neck malignancies in a single-arm prospective observational study. Forty-seven patients (29 inoperable lung carcinoma and 18 head and neck malignancies) were prospectively enrolled and underwent 99m Tc glucarate imaging [whole body planar and single-photon emission computed tomography of the region of interest] 4-5 hours after injection of 20 mCi of the radiopharmaceutical. Excellent 99m Tc glucarate concentration was noted in the target lesion in lung cancer and head and neck malignancies. The sensitivity was found to be better in lung cancer. Avid concentration of tracer was seen in the metastatic sites. During response evaluation, the glucarate concentration correlated well with the clinical and other radiological findings. 99m Tc glucarate showed avid concentration of tracer in the tumor, suggesting it to be a potential tumor imaging agent which can be used for detection and assessment of therapeutic response in malignancy.